2017
DOI: 10.1007/s40520-017-0872-y
|View full text |Cite
|
Sign up to set email alerts
|

Carrying heavy asymmetrical loads increases postural sway during quiet standing in older adults

Abstract: Holding asymmetrical loads in the hands is common during many daily and occupational activities which, depending on the load mass, may alter postural stability. The purpose of this study was to determine the effect of load magnitude held asymmetrically in the hand on postural sway in older people. Eighteen healthy older adults (age 65.9 ± 5.7 years) were assessed in the following conditions; (1) standing without an external load (0%), (2) standing while holding a grocery bag containing 5%, (3) 10% and (4) 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previous research has indicated that carrying externals loads elicits an increase in centre of pressure (COP) measures of postural sway during quiet standing [1][2][3][4][5] and stride-to-stride gait variability during walking [6,7]. These changes are important as load carriage during standing and walking is a common practice in different occupational and daily tasks [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that carrying externals loads elicits an increase in centre of pressure (COP) measures of postural sway during quiet standing [1][2][3][4][5] and stride-to-stride gait variability during walking [6,7]. These changes are important as load carriage during standing and walking is a common practice in different occupational and daily tasks [8].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the vast majority of research that has investigated the influence of external loading on postural sway and gait parameters has examined posterior (e.g. backpack) [1,4,5,8] or lateral (e.g., grocery bags) load carriage [2,[9][10][11]. Carrying external loads changes the massinertia characteristics of the body's centre of mass (COM).…”
Section: Introductionmentioning
confidence: 99%
“…The CGS during the eyes open condition was estimated using the trajectory lengths of before/after and left/right direction, total trajectory lengths, moving speed, and area component (GS variable) displaying the distance and scope of the center of pressure shaking (Hill & Price, 2018). Since healthy people have a high speed and twitch shaking in before/after and left/right direction (high-frequency shaking), but the patients with dizziness and equilibrium disorder have a low speed and large shaking (low-frequency shaking), the PS variables were used to estimate the periodic CGS in the patients (Demura et al, 2008).…”
Section: Estimation Variablesmentioning
confidence: 99%
“…Human's CGS primarily uses the center of pressure (Demura et al, 2006;Masani et al, 2007) and has been evaluated using general sway (GS) variables [such as before/after, left/right, total trajectory lengths, moving velocity, and area component; (Hill & Price, 2018)]. Uchiyama and Demura (2007) reported that a variation of the before/after and left/right directions increased in subjects with eyes closed owing to the blocked visual senses, as compared to those with eyes open.…”
Section: Introductionmentioning
confidence: 99%